Leading causes of excess mortality in Mexico during the COVID-19 pandemic 2020-2021: A death certificates study in a middle-income country - Lina Sofía Palacio-Mejía; Juan Eugenio Hernández-Ávila; Mauricio Hernández-Ávila; Dwight Dyer-Leal; Arturo Barranco; Amado D. Quezada-Sánchez; Mariana Alvarez-Aceves; Ricardo Cortés-Alcalá; Jorge Leonel Fernández- Wheatley; Iliana Ordoñez-Hernández; Edgar Vielma-Orozco; María de la Cruz Muradás-Troitiño; et al. (Elsevier, 2022)
Summary: Background: The death toll after SARS-CoV-2 emergence includes deaths directly or indirectly associated with COVID-19. Mexico reported 325,415 excess deaths, 34.4% of them not directly related to COVID-19 in 2020. In this work, we aimed to analyse temporal changes in the distribution of the leading causes of mortality produced by COVID-19 pandemic in Mexico to understand excess mortality not directly related to the virus infection. Methods: We did a longitudinal retrospective study of the leading causes of mortality and their variation with respect to cause-specific expected deaths in Mexico from January 2020 through December 2021 using death certificate information. We fitted a Poisson regression model to predict cause-specific mortality during the pandemic period, based on the 2015-2019 registered mortality. We estimated excess deaths as a weekly difference between expected and observed deaths and added up for the entire period. We expressed all-cause and cause-specific excess mortality as a percentage change with respect to predicted deaths by our model. Findings: COVID-19 was the leading cause of death in 2020-2021 (439,582 deaths). All-cause total excess mortality was 600,590 deaths (38⋅2% [95% CI: 36·0 to 40·4] over expected). The largest increases in cause-specific mortality, occurred in diabetes (36·8% over expected), respiratory infections (33·3%), ischaemic heart diseases (32·5%) and hypertensive diseases (25·0%). The cause-groups that experienced significant decreases with respect to the expected pre-pandemic mortality were infectious and parasitic diseases (-20·8%), skin diseases (-17·5%), non-traffic related accidents (-16·7%) and malignant neoplasm (-5·3%). Interpretation: Mortality from COVID-19 became the first cause of death in 2020-2021, the increase in other causes of death may be explained by changes in the health service utilization patterns caused by hospital conversion or fear of the population using them. Cause-misclassification cannot be ruled out. Funding: This study was funded by Conacyt.